(Dé)montrer la maltraitance parentale sur Instagram : Étude argumentative du récit extime catégorisant - Rose Moreau Raguenes (Cahiers de Narratologie)
This study investigates the process of extimacy – that is, the process of sharing fragments of the intimate self for validation by others (Tisseron 2011) – in narratives which were published anonymously on the Instagram account Parents toxiques. An overview of the account, with a particular focus on the parameters and stakes of the written and asynchronous interaction in which the narratives are produced, shows that the categorisation of the speakers’ parents and lived experiences is both a consequence and a condition for telling their story of abuse on Parents toxiques. I therefore aim to determine how extimacy is realised argumentatively in this particular digital environment; to this end, I carry out a discursive analysis of ten narratives published between May 2020 and January 2021. It appears that such narratives, which I propose to name categorising extimate narratives, acquire an argumentative dimension (Amossy 2018). The speakers construct a viewpoint (Rabatel 2018) on the events they recount – which, as a result, take on an argumentative function within the implicit demonstration. Moreover, the argumentative processes mobilised by the speakers are conceived as discursive traces of unresolvedness; therefore, they point to the object of validation which is targeted by the categorising extimate narrative. Ultimately, I argue that the Parents toxiques narratives are performative in that they allow speakers to renegotiate their relationship to their experience of abuse: the process of categorising extimacy and the resulting acknowledgement of their story allows them to co-construct, together with members of the community, the meaning attributed to their lived experiences and sufferings.